Perancangan Bumper Animasi Logo PT Santos Jaya Abadi Untuk Keperluan Orientasi Karyawan Baru - Agnes Delicia Husada; Cindy Cecilia Kim; Samuela Yosafa Isabel Anritan (Universitas Ciputra Surabaya, 2022)
This research contains the design process of the animated bumper of PT Santos Jaya Abadi logo for the new employee orientation program. New Employee Orientation Program doesn’t only serve as a starting point for the company’s introduction to new employees, it also plays a role in the employee’s adaptation process to the new working environment. Seeing the significance of this event, it is necessary to design interesting activities using the right media. Animated bumpers that are interactive and efficient are able to gain the attention of new employees during the orientation process and convey messages effectively. The research was conducted using qualitative methods through target audience interviews and literature studies. The objective of this research is to find out the characteristics of a suitable animated bumper design to be used during the orientation process for new employees of PT Santos Jaya Abadi. The results obtained show that the appropriate animated bumper for the new employee orientation process must not only have a concept and visuals that match the company, but also a relatable storyline, attractive visuals, and the right audio selection. Keywords: Animated Bumper, Logo Bumper, New Employee Orientation, Design.